MODERN CHALLENGES AND PRIORITIES OF THE SOCIAL AND HUMANITARIAN POLICY OF UKRAINE - MELNYCHUK, Dmytro; VOINALOVYCH, Iryna (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The research emphasizes the problem of aggravation and the need to solve the problems of social and humanitarian development of Ukraine and its regions. The purpose of the research is to generalize the challenges, as well as justify the priorities of the social and humanitarian policy of Ukraine with the aim of post-war recovery and preservation of human capital. It is shown that the key challenges of the social and humanitarian sphere of Ukraine in war conditions relate to: critically large volumes of refugees abroad, mass internal movements of the country's population, destabilization of internal regional labor markets, loss of income and the spread of population poverty, worsening and increasing the load on social welfare facilities infrastructure. The priority tasks of the state social and humanitarian policy in such conditions are defined: development of the educational infrastructure of communities and territories, improvement of the quality of educational services and activation of processes of strengthening social unity (in the educational component of patriotic education, integration of displaced persons and educational rehabilitation of combatants); restoring the sustainability of the health care system by deploying a network of hospital districts in accordance with the territorial specificity and needs of the population, creating coordination centers for tracking and distributing patients, improving the resource support of health care institutions in communities, using the potential of IDPs to overcome personnel "hunger" in the industry; solving the problems of housing provision for IDPs, increasing the efficiency of the functioning of the system of social support of the population, optimizing the territorial placement of objects of social support of the population in conditions of growing demand for social services; formation of banks and rational use of communal, social and service housing; alleviation of the threats of demographic disparities in the development of regions and territorial communities in accordance with the characteristics of their demographic development and post-war population resettlement in the regions of Ukraine.
Keywords: social and humanitarian development; state policy; state regulation; strategic tasks and priorities; human capital; human potential; challenges of war